REVITALISASI SITU TIPAR SEBAGAI WISATA BARU DI KOTA DEPOK - Binsar Farel Mohamad; Priyendiswara Agustina Bela; Parino Rahardjo; Regina Suryadjaja (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Depok city has now developed into one of the cities that experienced quite high growth in the JABODETABEK area. For the people of the city itself a comfortable city can not be met only with infrastructure development, but also required public space to interact and socialize one of them by utilizing the natural potential that exists as a recreational facility. Lake as a natural beauty with the form of protected areas has a function as a water importer (recharge) in groundwater basins, clean water reserves, land fisheries and recreational facilities. Situ Tipar is one of the four that is being prioritized to improve competitiveness in 2020. But for the existing condition of Situ Tipar still has some problems, namely the misuse of the border there, the lack of quality and quantity of public facilities and existing conditions that are not maintained so that the lake has not been able to facilitate tourists who come to Situ Tipar. On this basis, this research was carried out to provide recommendations to the government and surrounding residents to organize areas that improve the quality of Tipar in accordance with its function and positive impacts that can prosper the surrounding residents. This research refers to existing data and combined with the study of government and empirical regulations. The analysis method that the author uses is policy analysis, location, footprint, tourist attraction and best practices with descriptive analysis tools, SWOT and benchmarking Keywords:  City; Recreation; Situ AbstrakKota Depok kini telah berkembang menjadi salah satu kota yang mengalami pertumbuhan cukup tinggi di wilayah Jabodetabek. Bagi masyarakat kota sendiri kota yang nyaman tidak dapat terpenuhi hanya dengan pembangunan infrastruktur, tapi juga diperlukan ruang publik untuk berinteraksi dan bersosialisasi salah satunya dengan memanfaatkan potensi alam yang ada sebagai sarana rekreasi. Situ sebagai keindahan alam dengan bentuk kawasan lindung mempunyai fungsi sebagai pengimbuh (recharge) air pada cekungan air tanah, cadangan air bersih, perikanan darat serta sarana rekreasi. Situ Tipar merupakan salah satu situ dari empat situ yang sedang diprioritaskan pengembangunannya guna meningkatkan daya saing pada tahun 2020 ini. Namun untuk kondisi eksisting Situ Tipar masih memiliki beberapa permasalahan yaitu adanya penyalahgunaan sempadan situ, masih minimnya kualitas dan kuantitas fasilitas umum serta kondisi eksisting yang tidak terawat sehingga belum dapat memfasilitasi wisatawan yang datang ke Situ Tipar. Atas dasar tersebut maka penelitian ini dilakukan guna memberikan rekomendasi kepada pemerintah serta warga sekitar untuk melakukan penataan kawasan yang bersifat meningkatkan kualitas situ Tipar sesuai dengan fungsinya serta dampak positif yang dapat mensejahterakan warga sekitar. Penelitian ini mengacu kepada data eksisting dan dipadu dengan kajian peraturan pemerintah dan empiris. Adapun metode analisis yang penulis pakai adalah analisis kebijakan, lokasi, tapak, daya tarik wisata dan best practices dengan alat analisis deskriptif, SWOT dan benchmarking.